2016
DOI: 10.14311/ap.2016.56.0319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibre Aspect Ratio and Fibre Volume Fraction on the Effective Fracture Energy of Ultra-High-Performance Fibre-Reinforced Concrete

Abstract: <p>This paper investigates the effective fracture energy of UHPFRC with various fibre volume fractions and various fibre aspect ratios. We have concluded that the effective fracture energy is dependent on both the fibre volume fraction and the fibre aspect ratio. In addition, we have found that both dependencies follow a linear trend.</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
(44 reference statements)
0
10
0
2
Order By: Relevance
“…Plasticizer. In accordance with principles of high performance concrete production [20][21][22], a high amount of super-plasticizer (based on polycarboxylether) was applied to reduce the water to binder ratio to 0.25. This high dosage of plasticizer can cause changes during its burning and evaporation after the first thermal loading cycle.…”
Section: Composition Of Used Mixturesmentioning
confidence: 99%
“…Plasticizer. In accordance with principles of high performance concrete production [20][21][22], a high amount of super-plasticizer (based on polycarboxylether) was applied to reduce the water to binder ratio to 0.25. This high dosage of plasticizer can cause changes during its burning and evaporation after the first thermal loading cycle.…”
Section: Composition Of Used Mixturesmentioning
confidence: 99%
“…The fibres that were used to construct the UHPFRCC were straight and smooth with a length of 14 mm and aspect ratio of 108:1. It has been demonstrated in previous studies that a higher aspect ratio >100:1 results in a significantly higher flexural strength and also in a higher amount of energy dissipated during the fracture [20]. The number of fibres in the material body, which has been set to 1.5% in this study by volume, was derived from a reasonable trade-off between the performance and workability of the fresh mixture.…”
Section: Ultra-high-performance Fibre-reinforced Cementitious Compositementioning
confidence: 91%
“…According to the aspect ratio of fiber, as l/d increase, the toughness index increase. Where Nawy [46], Wang et al [47] and Sovják et al [48] mentioned that toughness is significantly improved as a function of the increasing of the aspect ratios of the fibers used. On the other hand, Homrich and Naaman [49] found that fiber length and aspect ratio affect the possible volume fraction of fibers that may be placed in molds, where a higher aspect ratio is reflected by a higher absolute number of fibers in the mixture which lead to more energy absorption and better crack control.…”
Section: Toughness Of Sifconmentioning
confidence: 99%